Functional inks and extrusion-based 3D printing of 2D materials: a review of current research and applications. Issue 37 (18th September 2020) - Hassan, Kamrul; Nine, Md Julker; Tung, Tran Thanh; Stanley, Nathan; Yap, Pei Lay; Rastin, Hadi; Yu, Le; Losic, Dusan
Abstract : Graphene and related 2D materials offer an ideal platform for next generation disruptive technologies and in particular the potential to produce printed electronic devices with low cost and high throughput. Abstract : Graphene and related 2D materials offer an ideal platform for next generation disruptive technologies and in particular the potential to produce printed electronic devices with low cost and high throughput. Interest in the use of 2D materials to create functional inks has exponentially increased in recent years with the development of new ink formulations linked with effective printing techniques, including screen, gravure, inkjet and extrusion-based printing towards low-cost device manufacturing. Exfoliated, solution-processed 2D materials formulated into inks permits additive patterning onto both rigid and conformable substrates for printed device design with high-speed, large-scale and cost-effective manufacturing. Each printing technique has some sort of clear advantages over others that requires characteristic ink formulations according to their individual operational principles. Among them, the extrusion-based 3D printing technique has attracted heightened interest due to its ability to create three-dimensional (3D) architectures with increased surface area facilitating the design of a new generation of 3D devices suitable for a wide variety of applications. There still remain several challenges in the development of 2D material ink technologies for extrusion printing which must be resolved prior to their translation into large-scale device production. This comprehensive review presents the current progress on ink formulations with 2D materials and their broad practical applications for printed energy storage devices and sensors. Finally, an outline of the challenges and outlook for extrusion-based 3D printing inks and their place in the future printed devices ecosystem is presented.